Industrial Minerals and Their Uses - A Handbook and Formulary - Ciullo, P.A. (Noyes Publications, 2011)
This multi-authored handbook is a unique cross-industry resource for formulators and compounders, and an invaluable reference for the producers of formulated commodities and industrial minerals.